СМАҒҰЛ САДУАҚАСОВ: МЕМЛЕКЕТ ЖƏНЕ ҚОҒАМ ҚАЙРАТКЕРІ (Journal of actual problems of jurisprudence, 2019)
In this article author considers activity of stately and public man Smagul Sadvakasov whish made own contribution inarrangement of Soviet Union power at Kazakhstan region and in returning Kazakh lands.